Using Byram’s Savoirs to Ensure the Incorporation of Intercultural Communicative Competence into Language Teaching - John Harper (Journal of English Language Teaching and Linguistics, 2023)
Although the term “intercultural communicative competence” (ICC) is often used in academic literature, studies indicate that the ICC element is often not included in the actual teaching practices of tertiary institutions. Due to the lack of ICC instruction across the curriculum, foreign language (FL) courses seem to stand out as logical sites for instruction in ICC. FL instructors, however, are not necessarily trained in matters of ICC, and the standard default method of acquiring ICC outside the language class (i.e., study abroad) is clearly not available to all students. In a global society, ICC is relevant for all students. This paper uses Byram’s 1997 savoirs (i.e., competences desirable of the “intercultural speaker”) as a starting point to provide evidence of tried and tested FL teaching practices that reveal ways in which ICC instruction may be incorporated into FL courses even in academic environments in which direct intercultural contact is unlikely. While recognizing the obstacles of teaching ICC in such environments, the study reveals that the inclusion of ICC is not only possible but necessary in them.